Sleeping beauties : the mystery of dormant innovations in nature and culture - Wagner, Andreas, 1967 January 26- (Oneworld Publications, 2023)
"Many animals and plants eke out seemingly unremarkable lives. Passive, constrained, modest, threatened. Then, in a blink of evolutionary time, they flourish spectacularly. Once we start to look, these "sleeping beauties" crop up everywhere. But why? Looking at the book of life, from apex predators to keystone crops, and informed by his own cutting-edge experiments, renowned scientist Andreas Wagner demonstrates that innovations can come frequently and cheaply to nature, well before they are needed. We have found prehistoric bacteria that harbour the remarkable ability to fight off 21st-century antibiotics. And human history fits the pattern too, as life-changing technologies are invented only to be forgotten, languishing in the shadows before they finally take off. In probing the mysteries of these sleeping beauties, Wagner reveals a crucial part of nature's rich and strange tapestry"--